PBL BERORIENTASI SDGs: STRATEGI UNTUK MENINGKATKAN LITERASI SAINS DAN KESADARAN LINGKUNGAN SISWA - Median Agus Priadi; Berti, Berti Yolida; Rini, Rini Rita T. Marpaung; Panggih, Panggih Priyambodo (Universitas Muhammadiyah Pontianak, 2025)
This study aims to determine the effect of the SDGs-oriented problem-based learning (PBL) model in improving students' scientific literacy and environmental awareness. The type of research used is a quasi-experimental. The research subjects were seventh grade SMPN 1 Gisting. consisting of classes VII A (experimental) and VII B (control), which were taken using purposive sampling technique. The experimental class was given treatment using the PBL model, while the control class used the discovery model. Data on scientific literacy skills were obtained from the results of the pretest and posttest and environmental awareness was obtained from the results of the questionnaire. Scientific literacy data were analyzed using the Independent Sample T-test. The results showed the Sig. (2-tailed) value of 0.001 <0.05. Environmental awareness also reached the “very good” category with an average score of 90.16%. The average N-gain value of the experimental class's scientific literacy skills (0.53) was higher than the control class (0.23). These findings indicate that the SDGs-oriented PBL model effectively strengthens students' scientific literacy and environmental awareness. The SDGs-oriented PBL model deserves to be prioritized in scientific learning because it has been proven to be more effective in increasing students' scientific literacy and environmental awareness.